Effect of the Covid-19 Pandemic on Stock Market Return With Macro Indicators as Control Variables in Indonesia and Malaysia - Arminta, Ega; Pangestuti, Irene Rini Demi (BISNIS, 2022)
This research aims to examine the positive COVID-19 variable, the COVID-19 death variable, the COVID-19 vaccination variable, and the currency exchange rate variable as a control variable for stock market returns in Indonesia and Malaysia. The population in the test is a combination of the main indexes of the Indonesian and Malaysian stock exchanges. Sample selection using a purposive sampling method. The analytical tool used in this study is multiple linear regression analysis with 104 observational data for the period 2021-2022. The test results show that the positive COVID-19 confirmation variable has no significant effect, the COVID-19 death confirmation variable has a significant positive effect, and the COVID-19 vaccination variable has no significant effect on stock market returns